METHODOLOGY OF COMPILING THE NATIONAL CORPUS OF THE UZBEK LANGUAGE AND ITS PROBLEMS - Toirova Guli Ibragimovna; Aziza Navro'zova Aslonovna (Journals Park Publishing, 2023)
The article discusses the types of interfaces and the importance of the search window of the corpus in the creation of the national corpus of the Uzbek language. The interface of the national corpus consists of various designs and structures, the author is responsible for their completeness, the interface should be attractive and effective. The creation of the interface is based on national or modern features, and the interface should focus on the national color. Linguistic corpora are a very fast-growing branch of the world of computational linguistics that has achieved great success. An interface is a communication system between a technology and a user. Interface types such as visual, gestural and linguistic were analyzed.
Keywords: interface, author's corpus, mathematical modeling, morphological and semantic annotation, information, linguistic basis, artificial intelligence, computational linguistics, corpus linguistics, language corpus, specialized software, electronic library, lexicon, morphological, grammatical, semantic signs and problems with linguistic signs.